Early Childhood Education Teacher Creativity Development Strategies as 21st Century Skills - Musnia Musnia; Asma Kurniati; Hartati Hartati (JED (Jurnal Etika Demokrasi), 2026)
The development of early childhood education teachers’ creativity is a critical issue in preparing young learners to acquire 21st-century competencies, particularly creative thinking, communication, collaboration, and critical thinking. However, previous studies on strategies for enhancing teacher creativity remain fragmented, creating a need for a systematic synthesis that can guide professional development in early childhood education contexts. This study aims to identify, analyze, and synthesize strategies for developing early childhood education teachers’ creativity as a 21st-century skill. This research employed a Systematic Literature Review approach guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework. The review process consisted of identification, screening, eligibility assessment, and inclusion stages. A total of 72 articles were initially identified from relevant early childhood education journals, and nine articles that met the inclusion criteria were selected for further analysis. The selected articles were examined using content analysis by identifying key findings, classifying recurring themes, and synthesizing strategy patterns related to teacher creativity development. The findings reveal that early childhood education teachers’ creativity can be strengthened through continuous professional training, mentoring, creative and contextual learning media, loose parts-based activities, arts integration, STEAM-based learning, project-based play, and empowering leadership. These strategies support teachers in designing innovative, adaptive, meaningful, and child-centered learning experiences. The study concludes that teacher creativity is not merely an individual attribute, but a professional competency that can be systematically developed through pedagogical innovation and institutional support. The novelty of this study lies in its synthesis of scattered empirical findings into an integrated framework aligned with 21st-century competencies. This study contributes to the development of evidence-based references for teacher professional development and creative learning practices in early childhood education.